Bronchial and bronchiolar carcinoma experiences in diagnosis - Middlemass, I. B. D. (The University of Edinburgh, 1961)
This study was made in an attempt to assemble ideas, to confirm or refute the views of other writers and to suggest uncomplicated investigations which are of diagnostic value in suspected cases of bronchial carcinoma. Comparisons are made with bronchial adenoma and a group of bronchiolar carcinomata is reviewed. A special study was made of the effects of bronchial carcinoma on the movements (28 cases) and contour (200 cases) of the barium -filled oesophagus and 500 cases of bronchial carcinoma which came to operation are reviewed. The main conclusions are: (1) There is a surprisingly small proportion of females (1 :13) in a group of bronchial carcinomata subjected to thoracotomy. (2) Bronchial adenoma is 10-20 times less common than is often suggested. (3) In spite of the right lung being larger than the left, an operative series of cases of bronchial carcinoma contains more tumours on the left than on the right side. Highest operability rates occur in tumours of the left lower lobe and lingula. (4) Epidermoid carcinoma accounts for two -thirds of cases which come to operation and three- quarters of those which are resected. (5) Very few cases of bronchial carcinoma were truly asymptomatic. (6) Haemoptysis requires careful investigation but considerable numbers of cases are seen in which no cause can be found. This symptom suggests that a peripheral "coin" lesion in the lung is most likely to be malignant. (7) The presence or absence of pain bears no constant relation to the extent of mediastinal spread from bronchial carcinoma. (8) Finger-clubbing occurred in 20 of cases of bronchial carcinoma. Epidermoid carcinoma was 4 times as common as anaplastic tumour in these cases and accordingly operability rates were slightly higher in cases with clubbing than in those without it. (9) Asymptomatic hypertrophie pulmonary osteoarthropathy was not found in any of 100 cases of finger -clubbing due to bronchial carcinoma. (10) Bronchoscopic biopsy provided a positive diagnosis in 57% of cases of bronchial carcinoma and in 87% of bronchial adenomata. In carcinoma, the highest incidence of positive findings at bronchoscopy occurred in the right lower lobe (79%) and the lowest in the middle lobe (31%). (11) Lateral oesophageal shift with respiration is an easily elicited sign of lower lobe or main bronchial stenosis. (12) More than 1 out of every 4 cases of bronchial carcinoma referred to a surgical clinic showed varying degrees of extrinsic pressure on the oesophagus, most frequently seen in the P.A. and L.A.O. positions. This is a highly reliable sign of inoperability and may be of considerable diagnostic value when bronchoscopy is negative. In 68% of cases showing oesophageal deformity the primary tumour was on the right side and in the same proportion the histology of the lesion was anaplastic carcinoma. (13) Fifteen out of 24 bronchial carcinoma M.M.R. pick -ups were inoperable. Only 4 were asymptomatic and 1 of these was inoperable. (14) Common errors in x -ray interpretation are reviewed and suggested remedies are: careful study of operative specimens, the collection and continual review of all known radiological errors, and the use of a series of test films to detect the "blind spots" of different radiologists. (15) Obstructive emphysema, unaccompanied by other radiological abnormalities, is a rare sign of bronchial carcinoma and apparently a very rare sign of early carcinoma. (16) 11% of cases of bronchial carcinoma were of peripheral type; 76% of these were operable. Lobulation of outline, frequently visible on plain films, was common but valueless in differential diagnosis. (17) Cavitation in a peripheral carcinoma occurred in 6.2% of cases; 74,b of these were in the left lung and none occurred in a female. Ope- rability rates were lower than in solid peripheral tumours. Different mechanisms probably operate to produce cyst -like cavities in different cases; only 3 out of 500 carcinomata showed this appearance. (18) Unilateral engorgement of interlobular septa in a case of bronchial carcinoma indicates inoperability. (19) Carcinoma arose in the middle lobe in 3.8% and in the lingula in 5% of cases; the latter were more frequently diagnosed by bronch- oscopy than the former. Middle lobe carcinoma is less common than would be expected from the size of the lobe itself but by no means as rare as has been suggested by some writers. Bronchoscopy is frequently negative in middle lobe carcinoma and evidence of oesophageal deformity at barium swallow may suggest the correct diagnosis. No case of the "middle lobe syndrome" was seen over the age of 35. (20) 75% of 12 cases in which a benign lesion was misdiagnosed as carcinoma occurred in the right upper lobe. Benign inflammatory conditions not infrequently take several months to resolve. Full radiological and clinical records of all cases wrongly diagnosed as carcinoma should be kept for ready reference at any time. Knowledge of the common sources of error should help to reduce misdiagnoses. (21) Thin, watery sputum occurred in only 1 out of 7 cases of bronchiolar carcinoma in which a satisfactory history was available. This symptom may also occur in cases of metastatic disease which can resemble bronchiolar carcinoma clinically, radiologically and even histologically. A correct diagnosis of bronchiolar carcinoma cannot be made from the radiological appearances when the lung lesion is solitary; it may be possible when lung shadows are multiple and full regard is given to the clinical picture. Bilateral disease is associated with an extremely poor prognosis but if a lesion is unilateral, resection may result in survival for several years.